PENDIDIKAN KARAKTER: MEMBANGUN PERILAKU SADAR SAMPAH PADA MASYARAKAT GAMPOENG MEURANDEH DAYAH, LANGSA LAMA - Makhroji Makhroji; Imam Hadi Sutrisno; Mufti Riyani (Global Science Society, 2020)
Community Service is intended as a preventive effort in handling and managing waste that has had a real impact on the community of Meurandeh Dayah Village. The impact in question is the reduced quality and quantity of water resources, increased cases of Malaria and dengue fever as well as the decreased environmental quality which is generally caused by low public awareness of waste-conscious behavior. Preventive efforts that are expected to touch the root of the problem are the application of character education to be able to build Waste Conscious Behavior in the Community. In general, character education can be applied by 1). Building the character of Caring for the Environment through example. The real step that can be taken is the Establishment of Trash Awareness Cadres. As role models, cadres need to be equipped with knowledge, attitudes, behavior, and skills in managing and processing waste properly and intelligently. 2). Building Character through habituation, one of the habituation activities can be initiated through the Waste Awareness Campaign Program for young peopleCommunity Service is intended as a preventive effort in handling and managing waste that has had a real impact on the community of Meurandeh Dayah Village. The impact in question is the reduced quality and quantity of water resources, increased cases of Malaria and dengue fever as well as the decreased environmental quality which is generally caused by low public awareness of waste-conscious behavior. Preventive efforts that are expected to touch the root of the problem are the application of character education to be able to build Waste Conscious Behavior in the Community. In general, character education can be applied by 1). Building the character of Caring for the Environment through example. The real step that can be taken is the Establishment of Trash Awareness Cadres. As role models, cadres need to be equipped with knowledge, attitudes, behavior, and skills in managing and processing waste properly and intelligently. 2). Building Character through habituation, one of the habituation activities can be initiated through the Waste Awareness Campaign Program for young generation